Young people lived experience of parental divorce with an emphasis on educational consequences - Reisi Sarteshneizy, Mojtaba (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Divorce has adverse effects on children and can have adverse effects on their mental and physical health. Also, divorce has negative effects on children’s education. Based on this, the aim of the present study was to investigate the lived experience of young people from their parents’ divorce, emphasizing the educational consequences. Methods: The present research method was qualitative with thematic analysis and applied in terms of purpose. The participants included high school students of Kurdish city in the academic year of 2022, who were selected purposefully. Some of the criteria for their selection were the experience of parental divorce and the desire to participate in the research. Also, the interviews were continued up to 14 cases based on the theoretical saturation criterion. For validity, face validity was used and for reliability, the agreement coefficient between coders was used, and the result of recoding was 0.86. For data analysis, manual coding method was used in the form of open, axial and selective coding. Results: The findings showed that 162 open codes, 13 core themes include: taunting by peers, blaming family, stigma of school environment, shame of divorce, family instability, children’s cold heart, emotional void, reluctance to study, excessive study fatigue, drop in academic mentality, Change in academic priority, academic aspirations, lack of morale and vitality, weak self-confidence, increased isolationism and increased introversion and 6 optional themes including: social stigma, cultural challenges, emotional challenges, poor education, academic conflict and psychological consequences for the lived experience of young people. Parental divorce was identified with an emphasis on educational outcomes. Conclusion: Based on the results, it can be concluded that divorce creates different and negative challenges for children and their education, which cultural and educational planners of the country can reduce the negative effects of these effects by empowering them.